Sistem Asuransi Beasiswa Berencana Pada Asuransi Jiwa Bersama Bumiputera 1912 Bandung - Widiya Avianti (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2023)
Scholarship Scheme the 1912 Bumiputera Joint Life Insurance Scheme is designed to provide education cost protection to insured children in accordance with their education program. Education and guaranteed income are two advantages of life insurance.. There are two types of insurance from the ten insurance programs offered by Asuransi Jiwa Bersama Bumiputera 1912 , namely : life insurance, including insurance for Planned scholarships. This study uses the method of case studies, and this study in the realm of qualitative to identify a particular issue. Uses in-depth datasets from multiple sources and detailed studies to explore limited settings over time. System design is presented in the form of context diagrams and E-R diagrams. The system needed to present information in management activities in Asuransi Jiwa Bersama Bumiputera 1912 Bandung is the calculation of premiums , learning Continuity Fund calculation system, and periodic scholarship calculation system.